STATISTICAL MODELING OF TOURISM INVESTMENT DECISIONS IN INDONESIA USING SEMIPARAMETRIC APPROACH - Yossy Maynaldi Pratama; Adji Achmad Rinaldo Fernandes; Ni Wayan Surya Wardhani; Nurjannah Nurjannah; Solimun Solimun (Barekeng)
The tourism potential in Indonesia is very large considering that Indonesia consists of tens of thousands of separate islands. Indonesia has many diverse landscapes, with all its nature wealth and biodiversity in it is an attraction for investors who want to invest in Indonesia.   The existence of relationships between variables that are linear and nonlinear, where no nonlinear pattern is known, requires a semiparametric approach. This study aims to apply a semiparametric approach to model people's investment decisions in tourism in Indonesia. The data used is in the form of respondents from investors who invest in tourism in Indonesia from the 2022 National Competitive Basic Research (PDKN) as many as 100 respondents. This study uses the semiparametric path analysis method to model tourism investment decisions in Indonesia. The results show that regulatory variables and investment interest variables have a significant and positive effect on investment decision variables. A diversity coefficient of 60.2% indicates that data diversity can be explained by 60.2% with models, while other variables outside the study explain the remaining 38.8%. In other words, the regulatory variable (X) and the investment interest variable (Y1) can influence the investment decision variable (Y2) by 60.2%.